High Rate and Long Lifespan Sodium-Organic Batteries Using Pseudocapacitive Porphyrin Complexes-Based Cathode - Chen, Xi; Feng, Xin; Ren, Bo; Jiang, Liangzhu; Shu, Hongbo; Yang, Xiukang; Chen, Zhi; Sun, Xiujuan; Liu, Enhui; Gao, Ping (Nano-Micro Letters, 2021)
Sodium-organic batteries utilizing natural abundance of sodium element and renewable active materials gain great attentions for grid-scale applications. However, the development is still limited by lack of suitable organic cathode materials with high electronic conductivity that can be operated stably in liquid electrolyte. Herein, we present 5,15-bis(ethynyl)-10,20-diphenylporphyrin (DEPP) and [5,15-bis(ethynyl)-10,20-diphenylporphinato]copper(II) (CuDEPP) as new cathodes for extremely stable sodium-organic batteries. The copper(II) ion partially contributes the charge storage and significantly stabilizes the structure of porphyrin complex for electrochemical energy storage. In situ electrochemical stabilization of organic cathode with a lower charging current density was identified which enables both improved high energy density and power density. An excellent long-term cycling stability up to 600 cycles and an extremely high power density of 28 kW kg−1 were achieved for porphyrin-based cathode. This observation would open new pathway for developing highly stable sodium-organic cathode for electrochemical energy storage. Highlights: 1 Functionalized porphyrin complexes are proposed as new pseudocapacitive cathodes for SIBs based on four-electron transfer. 2 The presence of copper(II) ion partially contributes the charge storage and significantly stabilizes the structure of porphyrin complex for electrochemical energy storage. 3 The electrochemical polymerization of porphyrin complex through the ethynyl groups in self-stabilization process contributes to high rate capability and excellent cycling stability.